Enantioselective C−H Functionalization Reactions under Gold Catalysis. Issue 20 (15th February 2022) - Das, Avishek; Patil, Nitin T.
Abstract: Transition metal‐catalyzed enantioselective functionalization of ubiquitous C−H bonds has proven to be promising field as it offers the construction of chiral molecular complexity in a step‐ and atom‐economical manner. In recent years, gold has emerged as an attractive contender for catalyzing such reactions. The unique reactivities and selectivities offered by gold catalysts have been exploited to access numerous asymmetric transformations based on gold‐catalyzed C−H functionalization processes. Herein, this review critically highlights the major advances and discoveries made in the enantioselective C−H functionalization under gold catalysis which is accompanied by mechanistic insights at appropriate places. Abstract : The gold‐catalyzed enantioselective C−H functionalization reactions has gained significant attention as it often provides complementary chemo‐ and regioselectivities as compared to other transition metal‐catalyzed processes. This review focuses on the recent developments in the field of enantioselective C−H functionalization reactions under gold catalysis and also highlights the mechanistic rationale at the appropriate places.